2015
DOI: 10.1111/cob.12114
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery and the risk of offspring overweight and obesity over the life course: a systematic review and bias‐adjusted meta‐analysis

Abstract: A causal role of Caesarean delivery (CD) on developing overweight and obesity in the life course of offspring has been postulated. However, the true strength of this association is not clear and the potential for confounding has not been adequately addressed. A systematic review and meta-analysis were conducted to evaluate the strength of this association, this time using a bias-adjusted model in addition to conventional methods. Our search yielded 32 estimates from 14 publications (n = 261,000) for meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 64 publications
6
68
0
2
Order By: Relevance
“…As shown in Table , six unique references provided 14 unique meta‐analyses of observational studies that assessed risk factors for obesity in adults. Sample sizes, ESs and prediction intervals of included meta‐analyses are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , six unique references provided 14 unique meta‐analyses of observational studies that assessed risk factors for obesity in adults. Sample sizes, ESs and prediction intervals of included meta‐analyses are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table , we identified 12 unique meta‐analyses of observational studies investigating associations of risk factors for obesity in children and adolescents, which were derived from 11 unique references, plus one that failed to show any nominally significant (ie P < 0.05) associations of weight gain during pregnancy and obesity during both childhood and adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…12,16 Several studies that included meta-analyses reported that children born by cesarean delivery were at higher risk of developing obesity, diabetes, or asthma in childhood. 4,6,30,31 The EPIIC hypothesis postulated by some of the authors in this paper, proposes that nonphysiological interventions during the intrapartum period, and specifically the use of synthetic oxytocin, epidural analgesia, and cesarean delivery, may interrupt the normal stress of being born. 10,11 This could have an epigenetic effect on specific genes, such as those that program immune responses, including weight regulation and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, other epidemiological studies did not report higher rates of asthma, diabetes type 1, obesity, and inflammatory bowel disease for children born with birth interventions 12, 16. Several studies that included meta‐analyses reported that children born by cesarean delivery were at higher risk of developing obesity, diabetes, or asthma in childhood 4, 6, 30, 31…”
Section: Discussionmentioning
confidence: 99%
“…A cesárea implica de modo negativo na saúde de lactentes e pode predispor problemas de saúde como asma, alergias, diabetes mellitus tipo 1, doença celíaca, sobrepeso e obesidade, que podem se manifestar da infância à idade adulta. 11 Durante o parto vaginal, o neonato é exposto à microbiota materna vaginal e fecal, levando à colonização por bactérias benéficas ao trato gastrointestinal, que proporcionarão uma menor probabilidade de disbiose, o que possivelmente seria um fator protetor contra a obesidade. Crianças nascidas de parto tipo cesárea apresentam nas primeiras 24 horas de vida microbiota fecal com maior similaridade com a microbiota da pele materna e com a presença de mais bactérias patogênicas quando comparadas a crianças nascidas de parto vaginal.…”
Section: Introductionunclassified